1994
DOI: 10.1007/bf00029895
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellins in seeds of Arabidopsis thaliana: biological activities, identification and effects of light and chilling on endogenous levels

Abstract: The activities of several gibberellins in stimulating germination of wild-type and GA-deficient gal seeds of Arabidopsis thaliana were compared. Of the six compounds tested GA4 and GAY-isolactone had the highest activity and GA7 and GA9 the lowest; activities of GA1 and GA3 were intermediate. Combined application of pure GAS presented no indications that more than one GA receptor is involved. Four GAS were identified in extracts from wild-type and GA-insensitive gai seeds by combined gas chromatography mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 27 publications
3
49
0
Order By: Relevance
“…Our in vitro enzyme assays have shown that the recombinant GA4H protein has enzymatic properties similar to GA4, including the substrate preference for GA 9 rather than GA 20 (Williams et al, 1998). This observation may reflect the predominance of non-13-hydroxylated GAs in Arabidopsis (Talon et al, 1990a(Talon et al, , 1990bDerkx et al, 1994) and is consistent with more efficient conversion of the non-13-hydroxylated substrate than the 13-hydroxylated precursor by the Arabidopsis GA 20-oxidases, which catalyze the formation of GA 9 and GA 20 (Phillips et al, 1995). In addition to the 3␤-hydroxylation of GA 9 and GA 20 , recombinant GA4 catalyzes 3␤-hydroxylation of C 20 GAs (GA 15 , GA 24 , and GA 44 ) and 2,3-epoxidation of 2,3-didehydrogibberellins with lower efficiencies (Williams et al, 1998).…”
Section: Ga4 and Ga4h Genes Are Differentially Expressed Although Thmentioning
confidence: 69%
See 3 more Smart Citations
“…Our in vitro enzyme assays have shown that the recombinant GA4H protein has enzymatic properties similar to GA4, including the substrate preference for GA 9 rather than GA 20 (Williams et al, 1998). This observation may reflect the predominance of non-13-hydroxylated GAs in Arabidopsis (Talon et al, 1990a(Talon et al, , 1990bDerkx et al, 1994) and is consistent with more efficient conversion of the non-13-hydroxylated substrate than the 13-hydroxylated precursor by the Arabidopsis GA 20-oxidases, which catalyze the formation of GA 9 and GA 20 (Phillips et al, 1995). In addition to the 3␤-hydroxylation of GA 9 and GA 20 , recombinant GA4 catalyzes 3␤-hydroxylation of C 20 GAs (GA 15 , GA 24 , and GA 44 ) and 2,3-epoxidation of 2,3-didehydrogibberellins with lower efficiencies (Williams et al, 1998).…”
Section: Ga4 and Ga4h Genes Are Differentially Expressed Although Thmentioning
confidence: 69%
“…In Arabidopsis, both the early 13-hydroxylation and the non-13-hydroxylation pathways are present in flowering shoots (Talon et al, 1990a(Talon et al, , 1990b and possibly in germinating seeds (Derkx et al, 1994). Therefore, we used both GA 9 and GA 20 as substrates to determine whether MBP-GA4H had 3 ␤ -hydroxylase activity (Figure 2A).…”
Section: In Vitro Functional Analysis Of the Ga4h Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…PAC totally repressed radicle protrusion. The addition of GA 4ϩ7 (Derkx et al, 1994) to the germination medium reversed this PAC inhibition. However, under these conditions, seed germination was somewhat more heterogeneous (T 50 Ϸ 2.2 d) than in the absence of PAC (Table I).…”
Section: Preparation Of Seed Samplesmentioning
confidence: 94%